Sex Differences in Lung Cancer Characteristics at Diagnosis: A Nationwide Register‐Based Study From the Faroe Islands (2015–2020) - Annika H. Lindenskov; Halla Potts; Marnar F. Kristiansen; Maria S. Petersen; Marin Strøm (Cancer Reports)
ABSTRACT Background Sex differences in lung cancer survival are well‐established, but the gap between Faroese men and women is especially pronounced. Faroese women have some of the highest 1‐ and 5‐year relative survival rates in the Nordic region, while Faroese men have some of the lowest. This study investigates these survival disparities by analyzing demographic, clinical, and temporal factors in Faroese lung cancer patients from 2015 to 2020. Methods All lung cancer cases registered in the Faroese Cancer Registry from 2015 to 2020 were included. Data on age, sex, civil status, cancer type, stage, smoking history, comorbidities, and performance status were extracted from electronic patient records. Sex‐based differences were analyzed and overall survival rates were estimated using Kaplan–Meier plots. Results Significant sex differences were observed in cancer staging at diagnosis (p = 0.03), with 25.8% of women diagnosed at Stage I compared to 8.8% of men. Gender‐specific patterns also emerged: women hadlonger symptomatic periods, while men experienced longer diagnostic and treatment times, though with overlapping confidence intervals. Conclusions Our findings reveal significant sex disparities in lung cancer staging at diagnosis in the Faroe Islands, which may the survival differences. The longer diagnostic period in men likely contributes to their lower survival rates. These results highlight the need for targeted interventions to reduce these disparities and improve patient outcomes.